Tindak Pidana Perzinaan sebagai Delik Aduan: Perbandingan Hukum Pidana Nasional dan Fiqh Jinayah - Usammah Usammah (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This study aims to examine the regulation of adultery as a complaint-based offence under Indonesian criminal law and to compare it with the concept of jarīmah hudūd in Fiqh Jinayah, with particular reference to Article 284 of the Indonesian Criminal Code (Kitab Undang-Undang Hukum Pidana/KUHP) and its reformulation under Article 411 of Law Number 1 of 2023. This research employs a qualitative library research design using a normative legal approach through the statute approach, conceptual approach, and comparative approach. Primary legal materials consist of statutory regulations, the Qur'an, Hadith, and ijmā', while secondary legal materials include scholarly books and peer-reviewed journal articles. The collected data were analysed using descriptive-analytical methods supported by content analysis. The findings reveal that Indonesian criminal law classifies adultery as a complaint-based offence aimed at safeguarding marital institutions and individual privacy, whereas Fiqh Jinayah categorises adultery as a jarīmah hudūd intended to preserve the objectives of maqāṣid al-sharī'ah through stringent evidentiary requirements. These normative differences substantially influence law enforcement mechanisms, evidentiary standards, sentencing philosophy, and the future direction of Indonesian criminal law reform in balancing legal certainty, human rights protection, and Islamic legal values.